Strategi Pengembangan Desa Wisata Halal di Kabupaten Samosir - Sinta Aulia Haikal; Yusrizal; Muhammad Ikhsan Harahap (Masyarakat Ekonomi Syariah Bogor, 2024)
The study aims to analyze the development strategy of the halal tourist village in the district of Samosir. The research was conducted using qualitative descriptive methods. Data was collected through semi-structured interviews of 17 informants obtained through purposive sampling techniques, closed questionnaires, and non-participant observations. Data is analyzed using descriptive analysis techniques and SWOT using IFAS and EFAS matrices. The results of the research showed that the internal factors that are the strengths of the development of Samosir halal tourism village are the potential of nature, regional culture, hospitality of the community, accessibility, facilities, and prices. While internal factors which are weaknesses are the professional SDM, supporting infrastructure, digital promotion, financial support, public participation, as well as the coordination of stakeholders. External factors that become opportunities include global halal tourist trends, central government support, accessibleness and infrastructures, information technology and digital marketing, interests of investment in the halal Tourism sector, and the empowerment of the village tourism community programmes. While the threats faced are competition of halal travel destinations, local tourist interests, synergy between stakeholder, regulatory support and policy risks, social conflict and resilience of the society, and risks of health crises and natural disasters. Future development strategies need to focus on internal turn-around towards balanced and sustainable growth and stability through enhanced SDM capacity, accelerated infrastructure, optimized digital promotion, increased public participation, and strengthened stakeholder coordination. The next strategy that can be applied is horizontal integration, which is to develop and integrate existing halal tourism products and services to be more complete and attractive to tourists.